Analysis of the Implementation of Maternal and Child Health Programs in Reducing Maternal and Neonatal Mortality Rates: A Study in the Anambas Islands, Riau Islands - Mafasya, Azhara; -Zahra, Az (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2025)
Maternal and neonatal mortality remains a significant public health challenge, particularly in remote and geographically isolated areas. This study examines the implementation of Maternal and Child Health (MCH) programs in the Anambas Islands, Riau Islands, and evaluates their effectiveness in reducing maternal and neonatal mortality rates. The research employs a mixed-method approach, combining quantitative data analysis from health records and surveys with qualitative insights from interviews with healthcare professionals and local communities. The findings indicate that while MCH programs, including antenatal care (ANC), skilled birth attendance, and emergency referral systems, have contributed to a decline in maternal and neonatal mortality, several challenges remain. Geographical barriers, limited healthcare infrastructure, transportation difficulties, and cultural preferences for traditional birth attendants hinder the full effectiveness of these programs. The study also highlights the role of trained midwives and community health workers in improving maternal health outcomes, though their reach is often constrained by logistical and resource limitations. Despite these challenges, the research confirms that MCH programs have positively impacted maternal and neonatal health in the Anambas Islands, though additional efforts are required to overcome geographical constraints, improve emergency response mechanisms, and enhance community-based health interventions. The study concludes that strengthening healthcare infrastructure, expanding mobile health services, and implementing culturally sensitive health education programs are crucial for further reducing maternal and neonatal mortality rates in remote island communities.